224. Effect of a Mobile App Chatbot and an Interactive Small Group Webinar on COVID-19 Vaccine Intention and Confidence in Japan: A Randomized Clinical Trial. (15th December 2022) - Yamada, Yuji; Tomoi, Hana; Nishina, Yuka; Harada, Ko; Tanaka, Kyuto; Sasaki, Shugo; Inaba, Kanako; Mitaka, Hayato; Takahashi, Hiromizu; Passanante, Aly; Lin, Leesa; Lau, Eric; et al.
Abstract: Background: Little is known about how social media platforms can be used to increase COVID-19 vaccine intent. We aimed to investigate the effect of social media-based interventions on vaccine hesitancy in Japan. Methods: We conducted a three-arm randomized controlled trial between 5 November 2021 and 9 January 2022. Japanese aged 20 or above who had not received any COVID-19 vaccine and did not intend to be vaccinated were randomly assigned to one of the following three groups: (i) a control group (with no intervention), (ii) a group with a free chatbot in a popular messenger app called 'LINE, ' which provided general information on COVID-19 vaccines and (iii) a group with free webinars where healthcare professionals interactively provided participants with the information on COVID-19 vaccines. The vaccine intention (VI) and three pre-defined Vaccine Confidence Index (VCI), including the importance, safety, and effectiveness of COVID-19 vaccines, were compared. Results: 1, 158 persons were included, and the baseline characteristics and demographics were balanced across three groups (Table 1). Among 386 persons assigned to the chatbot group, 231 (59.8%) accessed the chatbot and answered the post-survey. The post-survey revealed no significant difference in VI or VCI between the chatbot group and the control group (Table 2). Among 386 persons assigned to the webinar group, 207 (53.6%) attended webinars and answered the post-survey. The post-survey revealed no difference in VI between the webinar group and the control group. However, the VCI for the importance and the effectiveness significantly increased in the webinar group. There was no difference in VCI for the safety. VCI for the importance and the effectiveness in the control group decreased without any intervention during the study period. Vaccine intention and confidence after interventions Table 1 Table 2 Conclusion: While this study demonstrated that neither the chatbot nor the webinar changed VI, VCI for the importance and the effectiveness significantly increased with the webinar intervention. Interactive webinars with live Q and A provided by professionals may have a role in increasing COVID-19 vaccine confidence. Given the degree of vaccine hesitancy worsened over time in the control group, timely intervention is required. Disclosures: All Authors : No reported disclosures.